2020
DOI: 10.1002/cmdc.201900580
|View full text |Cite
|
Sign up to set email alerts
|

Targeting iNOS As a Valuable Strategy for the Therapy of Glioma

Abstract: Gliomas are the most prevalent primary tumors of the brain and spinal cord. Histologically, they share features of normal glial cells, but whether gliomas originate from normal glial cells, glial or neural precursors, stem cells, or other cell types remains a topic of investigation. The enhanced expression of inducible nitric oxide synthase (iNOS) has been reported as a hallmark of chemoresistance in gliomas, and several lines of evidence have reported that a decreased proliferation of glioma cells could be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Studies also revealed that lower amount of nitric oxide (NO) produced through inducible nitric oxide synthase (iNOS/NOS2) in various tumors, including gliomas, can promote angiogenesis, invasion, and cellular proliferation ( Fahey and Girotti, 2019 ; Maccallini et al, 2020 ). iNOS is a key regulator of glioma transformation downstream of the EGFRvIII/STAT3 signaling pathway.…”
Section: Glioma Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also revealed that lower amount of nitric oxide (NO) produced through inducible nitric oxide synthase (iNOS/NOS2) in various tumors, including gliomas, can promote angiogenesis, invasion, and cellular proliferation ( Fahey and Girotti, 2019 ; Maccallini et al, 2020 ). iNOS is a key regulator of glioma transformation downstream of the EGFRvIII/STAT3 signaling pathway.…”
Section: Glioma Tumor Microenvironmentmentioning
confidence: 99%
“…STAT3 directly binds to the promoter of the iNOS and thereby stimulates its expression ( Jahani-Asl and Bonni, 2013 ). Moreover, iNOS-derived NO in glioma cells elicits resistance to various therapies including 5-aminolevulinic acid (ALA)-based photodynamic therapy (PDT) and endows gliomas of greater proliferation and aggressiveness ( Fahey and Girotti, 2019 ; Maccallini et al, 2020 ). Several lines of evidence have showed that decreased proliferation of glioma cells could be mediated by selective inhibition of iNOS such as 1,400 W (N-(3-(aminomethyl) benzyl) acetamidine) ( Fedorov et al, 2003 ) or mercapto-ethyl guanidine (MEG) ( Southan et al, 1996 ) which inhibit the iNOS activity.…”
Section: Glioma Tumor Microenvironmentmentioning
confidence: 99%
“…Glioma is the most prevalent type of primary tumor of the central nervous system and accounts for >75% of malignant brain tumors (1,2). Histologically, glial-derived tumors, or gliomas, share characteristics of normal glial cells, glial or neural precursors and stem cells, and are generally named based on these similarities (3)(4)(5). Recent advances in molecular understanding have provided new insights and novel molecular subclassification of gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Also iNOS induction can cause inflammatory and autoimmune diseases, including septic shock, rheumatoid arthritis, diabetes, multiple sclerosis, and cancer. [14,15] The possibility of treating pathological conditions by selective inhibition of nNOS and iNOS could represent a feasible therapeutic strategy, and has stimulated an intense research effort. [16,17] On the contrary, NO produced by eNOS has mainly a physiological role, especially in maintaining vascular tone, and its inhibition should be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, aberrant nNOS induction can have detrimental consequences linked to the overproduction of NO, generating peroxynitrite and nitrosothiols; these highly reactive species can cause irreversible cell damage in excitotoxicity, ischemia, Parkinson's disease, Alzheimer's disease and depression [12,13] . Also iNOS induction can cause inflammatory and autoimmune diseases, including septic shock, rheumatoid arthritis, diabetes, multiple sclerosis, and cancer [14,15] . The possibility of treating pathological conditions by selective inhibition of nNOS and iNOS could represent a feasible therapeutic strategy, and has stimulated an intense research effort [16,17] .…”
Section: Introductionmentioning
confidence: 99%